Analysis of Switchgear on Insulation Performance and Reliability in Malaysian Railway Double Track Project - Sahari, Norain; Ngadiron, Zuraidah; Zulkifli, Dinie Amani; Ganasan, Reventheran; Ismail, Noramin; Kamaluddin, N.A. (2023)
Switchgears are the key component in protecting equipment in High Voltage (HV) settings. With the rise of railway projects in Malaysia, there will be an increase in demand for switchgear for the electrification project. Therefore, the type of switchgear that is better in terms of insulation performance and reliability needs to be determined. Then, a simulation model is developed in order to measure the Partial Discharge (PD) in the insulation medium of the switchgears. An analysis is conducted in order to compare which insulation medium is superior for switchgear. It is found that Sulfur-Hexafluoride (SF6) gas is seen to have lower values of peak voltage during PD inside the insulation medium compared to air. SF6 gas proves to be the better insulation medium compared to air in terms of insulation performance and reliability due to the lower values of peak voltage detected during the occurrence of PD. The finding of insulation performances will enhance the quality of Malaysian railways in order to decrease the breakdowns and disturbances related to the electrification system.